Organisational barriers to accessing vaccination services: a literature overview focusing on underserved populations in Europe. (30th September 2020) - Jansen, D
Abstract: Background: Immunization and equitable access to immunization are core components of the right to health (WHO). Although more and more children in the WHO European Region are being vaccinated against measles than ever before, coverage gaps even persist within countries. As a result, specific, underserved populations are left unprotected, resulting in a record number of these populations affected by the virus in 2018. Aim of this presentation is 1) to explore barriers that underserved populations might encounter and 2) share good examples of organisation of vaccination services for underserved populations. Methods: Literature searches have been conducted in a variety of databases, using different search terms. Published studies in English that explores 1) barriers in the organization of care; 2) successful interventions related to the organization of care, in (expected) low vaccination uptake populations will be included. The databases will extend beyond the medical literature to include social science literature. The literature search included peer reviewed international academic literature and government reports dating from 2010 to 2019. Results: In this presentation the results of the literature review will be presented: what barriers in the organization of care are experienced by populations that have low vaccination uptake? And what evidence does the literature present concerning the organisation of care that lead to a sufficient to high uptake of vaccination in populations where you would not expect this? Conclusions: the results of the literature review will provide a useful and valuable overview of barriers and facilitators of accessing vaccination services of (expected) low uptake populations in Europe. Since access, as a key dimension of organisation of care, is still the main factor hindering vaccine uptake it is important to learn lessons not only from poor practices but also from good practices.